Sosialisasi dan Pendampingan Penyusunan Kurikulum Operasional Satuan Pendidikan bagi Guru-guru PAUD - Tamelab, Ella; Nalle, Efraim Semuel; Radja, Petrus Logo; Saefatu, Irony Damianus; Lauren, Fua Susana (Devotion: Jurnal Pengabdian Masyarakat, 2024)
This community service activity aims to disseminate and help develop the operational curriculum for early childhood education teachers in Klasis Amanuban Selatan. The community service implementation team from IAKN Kupang carries out this socialization and mentoring activity to address the need for more understanding among PAUD teachers regarding the new Merdeka Curriculum. The training will also enhance the teachers' ability to create effective teaching materials that align with the curriculum, thereby improving the quality of early childhood education. The expected outcomes include the development of operational curriculum tools, the publication of an article, and enhanced educational practices in the targeted area. This community service activity also serves as a platform for creating an environment where teachers can exchange knowledge and experiences, ultimately leading to better educational outcomes for children. Through this initiative, PAUD teachers will be better equipped to implement the Merdeka Curriculum, thus contributing to the enhancement of early childhood education standards in Southern Amanuban.